A Review of Slow- and Fast-Light Based on Stimulated Brillouin Scattering in Future Optical Communication Networks - Ronny Henker; Andrzej Wiatrek; Kai-Uwe Lauterbach; Markus Junker; Thomas Schneider; Max J. Ammann; Andreas T. Schwarzbacher (Communications - Scientific letters of the University of Zilina, 2008)
Slow- and Fast-Light has been investigated during the last years as a powerful tool to reduce and increase the group velocity of light pulses by light. It has enjoyed much recent interest because of the practical applications for telecommunication and information systems. Among these are optical signal processing, radio frequency-photonics, nonlinear optics and time domain spectroscopy. Furthermore, it can be seen as a key technology for optical delay lines, buffers, equalizers and synchronizers in packet switched networks. For a realization, there are different methods and material systems possible. Among them the nonlinear effect of stimulated Brillouin scattering (SBS) is of special interest. This article gives an overview about the fundamentals and some experimental results of the Slow- and Fast-Light effect based on the SBS in optical fibers.